The Relationship of Academic Burnout and Internet Addiction in Academic Achievement: The Mediating Role of Optimism in Students - Novian Candra Kurniawan, Candra; Khusnul Khotimah; Zerina Nurkhamamah (LPPM Universitas Terbuka, 2024)
For students, academic achievement is significant. In addition to providing motivation, academic achievement also makes it easier for students to continue to the next level of education. However, academic burnout and internet addiction sometimes prevent them from achieving academic achievement. Therefore, this study examined the relationship between academic burnout and internet addiction. This study also includes optimism as an intervention variable. The research method used in this study is quantitative with explanatory type. The population in this study were ninth-grade students at SMP Negeri 11 Malang, with a sample of 72 students using the Slovin formula. Data were collected using a questionnaire, which was then distributed to respondents. One hundred fifteen respondents were obtained, and the results were then analyzed using partial least squares with the help of the SMART-PLS application. Direct and indirect results, such as overall academic burnout, hurt academic achievement and optimism. However, positive results were shown for internet addiction on academic achievement and optimism. This finding implies that excessive tasks and responsibilities lead to burnout and decreased academic performance. However, internet addiction in students can have a positive impact if used as a relevant learning resource.